Primary mucinous cystadenocarcinoma of the pelvic retroperitoneum in a male - Williams, Andrew K.; Boyle, Shawna L.; Chan, Susanne M.; Martinez, Carlos H; Lu, Chen; Chin, Joseph L. (Canadian Urological Association Journal, 2013)
Primary mucinous cystadenocarcinoma of the retroperitoneum is an extremely rare malignancy with only 2 male patients reported in the literature. We describe an unusual case presenting as a pelvic mass in a male with previous pan-proctocolectomy and end ileostomy for Crohn’s disease and review the available literature.